PHOTOBIOMODULATION THERAPY AS AN ADJUNCT TO GINGIVAL GRAFT FOR THE MANAGEMENT OF GINGIVAL RECESSION - A SYSTEMATIC REVIEW AND META-ANALYSIS - Poonam Rai,; Yashashree Chande,; Ankita Deshmukh,; Kanchan Deshmukh,; Nikita Patil,; Suyog Dharmadhikari, (The Bioscan, 2025)
BACKGROUND: This study aimed to systematically evaluate the effectiveness of photobiomodulation therapy as an adjunct to gingival grafting technique in the management of patients with gingival recession defects. METHODS: A comprehensive literature review was performed, including PubMed and the Cochrane Library, published up to and including December 2023. There were no restrictions on the date of publication. Articles available in English were included. Using the Cochrane Collaboration tool, we assessed the risk of bias for randomized controlled trials. A meta-analysis was performed on the relevant studies. RESULTS: Twelve randomized controlled trial were included. The standardized mean difference for Gingival recession depth between both the groups favored the PBMT+GG group showing a statistically significant difference (SMD, -0.81, 95% CI = -1.38 - -0.24, p – 0.005, I2- 75%). Standardized mean difference for width of keratinized tissue between both the groups showed a statistically significant difference between the groups (SMD, 0.47, 95% CI = -0.07 - 1.00, p – 0.09, I2- 77%) favoring the PBMT+GG group. The standardized mean difference for probing depth between both the groups favored the PBMT+GG group but did not show statistically significant difference (SMD, -0.08, 95% CI = -0.32 - 0.15, p – 0.49, I2- 0%). The standardized mean difference for clinical attachment loss between both the groups favored the PBMT+GG group showing a statistically significant difference (SMD, -0.63, 95% CI = -1.08 - -0.17, p – 0.007, I2- 78%). the standardized mean difference for post-operative pain between both the groups favored the PBMT+GG group showing a statistically significant difference (SMD, -1.29, 95% CI = -2.23 - -0.36, p – 0.007, I2- 91%). CONCLUSION: We concluded that the present systematic review can contribute to answering questions about the effectiveness of Photo biomodulation therapy on periodontal soft tissues during surgical procedures, considering the limitations we found that photo biomodulation therapy showed additional benefit in the long term when associated with connective tissue graft in the treatment of Miller Class I and II gingival recessions, also it improves the rate of wound healing and patient comfort in the immediate post-operative period. However, care must be used when interpreting the findings of this systematic review because of the small number of included studies and considerable heterogeneity in the laser parameters. Thus, more studies are needed to obtain more conclusive feedback.